2021
DOI: 10.1111/ane.13473
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neck motor control in chronic whiplash and tension‐type headache

Abstract: Objectives The purpose of this study is twofold, first to present a new method based on head laser tracking designed to measure head or hand movements and second to further investigate if patients suffering from chronic whiplash or tension‐type headache have impaired motor control of neck muscles. Material and Methods A new laser tracking instrument was designed to measure the ability of a test person to track a reference point moving on the wall by a laser fixed to the forehead or held in the hand. The refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In the present context of a possible central cause of this condition, it is of particular interest that tension-type headache patients display discoordination of head movements and discoordination of adjacent muscle groups. The discoordination of head movements was first observed by Woodhouse and Vasseljen (3) and Kristjansson and Oddsdottir (4) using 'the fly method' and recently confirmed by Astrup et al (5) using the laser tracking technique. This evidence indicates impaired neuromotor control by the central nervous system.…”
Section: Introductionmentioning
confidence: 80%
“…In the present context of a possible central cause of this condition, it is of particular interest that tension-type headache patients display discoordination of head movements and discoordination of adjacent muscle groups. The discoordination of head movements was first observed by Woodhouse and Vasseljen (3) and Kristjansson and Oddsdottir (4) using 'the fly method' and recently confirmed by Astrup et al (5) using the laser tracking technique. This evidence indicates impaired neuromotor control by the central nervous system.…”
Section: Introductionmentioning
confidence: 80%
“…In more recent studies, it has been suggested that chronic WAD (I–II) is a non-specific neck pain condition, a “ de novo ” tension-type headache, as clinical features are similar to non-specific low-back pain conditions ( 24 ). Shared mechanisms for so-called spinal dyssynergia might underlie the basis for motor disability, non-recovery, and poor treatment results when applying known physical rehabilitation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have observed subclinical but significant dyscoordination of head movements in whiplash as measured by “the fly method” ( 22 , 23 ) and recently by laser tracking ( 24 ). Other muscular systems adjacent to the neck musculature are also affected.…”
Section: The Natural Course Of the Whiplash Diseasementioning
confidence: 99%
“…Other muscular systems adjacent to the neck musculature are also affected. This is indicated by dyscoordination of eye movements ( 25 , 26 ) and the upper extremity ( 24 , 27 , 28 ). The dyscoordination of head movements probably is indicative of neuromotor hyperactivity and altered activation patterns as observed in the EMG studies.…”
Section: The Natural Course Of the Whiplash Diseasementioning
confidence: 99%